2010
DOI: 10.5114/wo.2010.979
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selected nutritional components in lung cancer risk – unsaturated fatty acids, isothiocyanates, selenium

Abstract: W Polsce w 2006 r. stwierdzono prawie 126 tys. nowych przypadków zachorowań na wszystkie nowotwory złośliwe i zarejestrowano ok. 91,5 tys. zgonów. W grupie kobiet po 65. roku życia najczęstszą przyczyną zgonów związanych z chorobą nowotworową był rak płuca, natomiast wśród mężczyzn zaobserwowano spadek zachorowalności i umieralności na ten rodzaj nowotworu, co wiąże się ze zmniejszeniem odsetka osób palących papierosy. Zaprzestanie palenia należy do podstawowych zaleceń profilaktyki pierwotnej. Duże znaczenie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The protective effects of selenium in the etiology of cancer diseases result from its effect on cell membranes protecting against oxidative stress, and also from the stabilizing effect on DNA and enhancement of cellular immune response [1,87]. It has also been found that selenium inhibits tumor cell proliferation via the effect exerted on the expression of p53 tumor suppressor gene, and Bcl-2 apoptosis-suppressor gene [101]. It has been shown that in the case of cancer occurrence, lesions in the p53 gene are reported [102].…”
Section: Influence Of Selenium In Cancer Preventionmentioning
confidence: 99%
“…The protective effects of selenium in the etiology of cancer diseases result from its effect on cell membranes protecting against oxidative stress, and also from the stabilizing effect on DNA and enhancement of cellular immune response [1,87]. It has also been found that selenium inhibits tumor cell proliferation via the effect exerted on the expression of p53 tumor suppressor gene, and Bcl-2 apoptosis-suppressor gene [101]. It has been shown that in the case of cancer occurrence, lesions in the p53 gene are reported [102].…”
Section: Influence Of Selenium In Cancer Preventionmentioning
confidence: 99%
“…Also, the protective effects of Se in the etiology of cancer result from its effect on cell membranes protecting against oxidative stress, and the stabilizing effect on DNA and increase of cellular immune response. It has been indicated that Se inhibits tumor cell proliferation via the effect exerted on Bcl-2 apoptosis suppressor gene and the expression of p53 tumor suppressor gene [ 18 , 22 ]. Protein hydrophobic interactions induced by a variety of nutritional and environmental factors can provide rational explanation for a number of pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%